PKM Olahan Gurita Khas Bengkulu Dan Wisata Bagi Peningkatan Ekonomi Masyarakat Pesisir - Ertanto, Dody; Apriansyah, Dolly; Putra, Dwingki Marta (Yayasan Rahmat Islamiyah, 2025)
This Student Creativity Program (PKM) aims to develop innovative processed octopus products typical of Bengkulu, characterized by a unique taste, high nutritional value, and longer shelf life. The processed products are packaged with attractive designs and integrated with coastal culinary tourism promotion, thereby increasing the interest of both local and international tourists. The implementation methods include surveys of raw material potential, training in processing and packaging, as well as marketing strategies based on digital platforms and tourism. The expected outcomes are the creation of Bengkulu’s signature processed octopus product as a regional culinary icon, increased income for coastal communities through business diversification, and the realization of synergy between the fisheries and tourism sectors.